Colloidal Mn2+ doped 2D (n =1) lead bromide perovskites: efficient energy transfer and role of anion in doping mechanism - Haris, Muhammed; Bakthavatsalam, Rangarajan; Kundu, Janardan (ChemistrySelect, 2018)
Mn²⁺ doping directly into APbCl3 type 3D nanocrystals, manifesting host to dopant energy transfer, have been heavily reported for illumination and display applications. However, these doped 3D ABX3 systems have low/modest exciton binding energy. Strongly bound excitons in the doped system can enhance the dopant‐host carrier exchange interactions leading to efficient energy transfer. Reported here is a simple and facile synthesis of colloidal Mn²⁺ doped (Butylammonium/octylammonium)2PbBr4 2D (n=1) perovskites that demonstrate enhanced energy transfer from strongly bound excitons of the host material to the Mn²⁺ dopant ions resulting in intense orange‐yellow emission due to spin forbidden internal transition (⁴T1 → ⁶A1) with the highest quantum yield (Mn²⁺) of 36%. Consistent with experimental evidences presented here, mechanism of this thermally aided doping process in these 2D systems, very likely, involves halide vacancy and its diffusion that precedes the cation exchange (doping) process. Owing to the high quantum yield, stability in ambient atmosphere, simplicity and scalability of the synthetic procedure, Mn²⁺ doped 2D perovskites could be beneficial as color converting phosphor material and can be utilized to further explore their magneto‐optoelectronic properties.